Relasi Sosial-Politik Indonesia dengan Ekspresi dan Pemaknaan Cinta - Fikrazamy Ghifari; Septiawan Santana Kurnia (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This research is sparked by the expression and deep meaning of love influenced by a grand narrative, exploring how social environments and state systems can impact an individual's personal space. This idea is encapsulated in the lyrics of